The Interpretation of Metaphor Ciphering Ideal Concept of Anak Gadih (Girl) in Malam Bainai Ritual in Minangkabau - Fithratul Miladiyenti; Djusmalinar Djusmalinar (Politeknik Negeri Padang, 2022)
This research analysed the interpretation of metaphor ciphering ideal concept of anak gadih (girl) in Malam Bainai ritual in Minangkabau. This research was qualitative research by means of semiotic analysis. The interpretation of metaphor was conducted by analysing the vehicle-topic mapping focused on observing the relational and referential aspects of the sign in the metaphor as a complex sign. The observation of relational and referential aspects was conducted by using Danesi-Perron’s metaphor theory (1999) and Peirce’s trichotomy model. The results of this research showed that the interpretation of metaphor is closely related to the vehicle (representamen)-topic (object) mapping deciphering cultural wisdom messages (interpretant). The representamens represent the values of cultural wisdom through their functions, characteristics, benefits, and unique conditions.